Mitochondrial dysfunction and alveolar type II epithelial cell senescence: The destroyer and rescuer of idiopathic pulmonary fibrosis - Liu, Suqi; Xi, Qian; Li, Xuannian; Liu, Huaman (Frontiers in Cell and Developmental Biology, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic respiratory disease with an unknown origin and complex pathogenic mechanisms. A deeper understanding of these mechanisms is essential for effective treatment. Pulmonary fibrosis is associated with the senescence of alveolar type II epithelial (ATⅡ) cells. Additionally, ATⅡ senescence can lead to a senescence-associated secretory phenotype, which affects cellular communication and disrupts lung tissue repair, contributing to the development of IPF. The role of mitochondrial dysfunction in senescence-related diseases is increasingly recognized. It can induce ATⅡ senescence through apoptosis, impaired autophagy, and disrupted energy metabolism, potentially playing a key role in IPF progression. This article explores the therapeutic potential of targeting cellular senescence and mitochondrial dysfunction, emphasizing their significant roles in IPF pathogenesis.